From Anxiety to Adaptation: How EFL Students Cope with Writing Challenges - Arini Nabilla Dzulfahmi; Rafila Kasamira Dewi Abrori; Dewi Puspitasari; Bouchra Aboura (Nexus Publishing, 2026)
This study aims to investigate writing anxiety among English Education students at UIN Abdurrahman Wahid Pekalongan. Employing a qualitative approach, data were collected through semi-structured interviews with seven third-semester students and analyzed using thematic analysis. The findings reveal that students experience significant writing anxiety manifested in cognitive, emotional, and physical challenges, including difficulties in generating ideas, organizing content, and fear of making errors. These challenges negatively affect students’ writing performance. Despite these difficulties, students employ various coping strategies, such as extensive reading and regular writing practice, to reduce anxiety and improve their writing skills. The study highlights the importance of addressing both cognitive and affective factors in supporting students’ writing development in EFL contexts.